A comparative analysis of the cost of cash retention and retention bond / Bashir O. Ganiyu … [et al.] - Ganiyu, Bashir Olanrewaju; Ola-awo, Wasiu Adeniran; Adetoro, Kabir; Umar, Moh’d Kabir (Faculty of Architecture, Planning & Surveying, 2015)
The practice of cash retention has been identified to be an opportunity cost to the contractor, equivalent to interest loss on cash retained, which could amount to a huge sum for larger contract. Literature revealed the use of retention bond as the best solution to the problems of cash retention. Hence, the need to evaluate and compare the cost of ‘cash retention’ and ‘retention bond’ costs to the contractor. This study will assist in improving payment practice in the construction industry and also improves financial stability of the contractor. Data were collected from interim valuations of completed projects and subsequently analyzed using “compounding method” to evaluate the compound interest loss on cash retained by the client and the cost of providing retention bond in-lieu of cash retention. T-test analysis was further used to determine the level of significance of the difference between both costs. The results of both analyses reveal that there is a significant difference between both cost and the utilization of retention bond in-lieu of cash retention will reduce the cost of retention by 65%. Subsequent to the findings of this research, it is therefore suggested that, clients should adopt retention bond in-place of cash retention as this will reduce the cost of retention to the contractor, while still providing adequate level of security to the clients’ money.